EFFECTS OF REDUCED FOREIGN TOURISM ON THE OPERATIONS OF YAOWARAT SMALL RESTAURANTS AMID COVID-19: A CASE STUDY - Pham Nguyet, Thao (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2024)
The COVID-19 pandemic caused a global health crisis and had a significant impact on businesses, particularly small restaurant businesses in Bangkok's Yaowarat Road area. This study examined the effects of the pandemic on small restaurant operations in this location and aimed to understand owners' perceptions of the impact of reduced foreign tourism on their businesses. Data was collected through a quantitative survey (n=75) and short interviews with restaurant owners, and statistical analysis was conducted using descriptive analysis, paired sample t-tests, and Pearson correlation analysis. The study found that the decline in foreign tourists and operational restrictions significantly affected small restaurant operations in terms of fewer customers, less revenue, and less employee work time. This study's finding offers insights into specific government programs that were deemed most helpful to these small businesses such as Lower Social Security Contributions and We Travel Together (Rao Tiew Duay Kan) Program. Recently the program We Travel Together has been extended to help businesses recover from the pandemic.